Management of Adolescent Gynecomastia: An Update - Soliman, Ashraf T; De Sanctis, Vincenzo; Yassin, Mohamed (Acta Biomedica Atenei Parmensis, 2017)
Gynecomastia refers to an enlargement of the male breast caused by benign proliferation of the glands ducts and stromal components including fat. It is the most common form of breast swelling seen in adolescent males. During pubertal development, gynecomastia can develop as a result of transient relative imbalances between androgens and estrogens. Pubertal gynecomastia is self-limited in 75 to 90% of adolescents and regresses over 1 to 3 years. However it may cause significant psychological stress and depression in adolescents. For boys with persistent gynecomastia that is causing substantial tenderness or embarrassment a tailored approach of close follow-up and use of anti-estrogen drugs may be recommended. These drugs block the effects of estrogens in the body and can reduce the size of the breasts somewhat. It appears that pharmacological therapy of persistent adolescent gynecomastia is reasonable effective if given early in the course of the disease and more successful in cases with small or moderate breast enlargement. However, neither of these drugs is universally approved for the treatment of gynecomastia because the risks and benefits have not been studied completely. Surgical approach may be needed under special conditions for cosmetic reasons. In this update, we review the different published trials for managing adolescent gynecomastia.